A high-uniformity silicon-based composite material, a preparation method and application thereof
Patent Information
- Application Number
- CN202210464679.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-04-29
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2042-04-29
AI Technical Summary
[0004]但是其充放电过程中体积膨胀现象导致电极结构破坏严重,容量急剧衰减,导致循环性能较差,另外SiOx本身较低的导电性也限制了材料电性能的发挥
[0031]所述碳包覆层的质量占高均匀性硅基复合材料总质量的0-20%。
Smart Images

Figure CN117012909B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of materials technology, and in particular to a highly uniform silicon-based composite material, its preparation method, and its applications. Background Technology
[0002] The current growth trend of new energy vehicles will lead to a sustained increase in demand for anode materials. Currently, natural / artificial graphite remains the dominant anode material for lithium-ion batteries globally, while novel anode materials such as mesophase carbon microspheres (MCMB), lithium titanate, silicon-based anodes, HC / SC, and lithium metal are also experiencing rapid growth.
[0003] Silicon-based anode materials, currently possessing the highest theoretical specific capacity, hold considerable promise. Successful application could significantly boost battery energy density. Silicon suboxide (SiO) is a major anode material in silicon-based anodes, exhibiting a high theoretical specific capacity (2680 mAh / g). Within the particles of SiO, crystalline nano-Si clusters are dispersed within a continuous medium of amorphous SiO2. Nano-Si is the primary source of the reversible capacity of the SiO anode, while the amorphous SiO2 undergoes an irreversible reaction during the initial lithium insertion cycle to generate lithium silicate and lithium oxide, providing a stable matrix to buffer the volume changes during the lithium insertion / extraction process of the nano-Si clusters.
[0004] However, the volume expansion during charging and discharging causes severe damage to the electrode structure, resulting in a sharp capacity decay and poor cycle performance. Additionally, SiO2... x The inherently low conductivity of SiO2 also limits the development of the material's electrical properties. To address this... x To address the problems of volume expansion, low conductivity, and low initial efficiency in anode materials, this invention provides a silicon suboxide with a uniform internal distribution of lithium, carbon, and SiC, and its preparation method. First, silicon powder is mixed with a carbon source to obtain silicon powder coated with the carbon source. Then, the carbon-coated silicon powder, silicon dioxide powder, and a lithium source are heated under reduced pressure to obtain corresponding vapors. These vapors are then rapidly cooled, deposited, and pulverized to obtain silicon suboxide with a uniform internal distribution of lithium, carbon, and SiC. This silicon suboxide with a uniform internal distribution of lithium, carbon, and SiC can effectively improve the first-cycle coulombic efficiency of the battery, as well as enhance the material's cycle performance and rate capability. Summary of the Invention
[0005] This invention provides a highly uniform silicon-based composite material, its preparation method, and its application. By pre-coating silicon powder with carbon elements, a silicon / carbon composite material is formed. The carbon elements and SiC generated under reduced pressure and high temperature heat treatment are uniformly distributed throughout the deposition stages, with no difference in content due to the order of deposition. This effectively ensures the uniformity of all deposited matrices. Simultaneously, the uniformly distributed carbon elements and SiC can buffer volume expansion during charge and discharge, suppress alloy pulverization, and enhance the conductivity of the silicon-based composite material. The addition of lithium source material compensates for lithium loss during the first charge and discharge cycle, improving the battery's first-cycle coulombic efficiency. This invention's highly uniform silicon-based composite material, through the combined action of carbon source co-coating silicon powder and lithium elements, yields a highly uniform silicon-based composite material of lithium, carbon, and SiC, thereby improving the battery's first-cycle coulombic efficiency, cycle performance, rate performance, and consistency.
[0006] In a first aspect, embodiments of the present invention provide a highly uniform silicon-based composite material, the highly uniform silicon-based composite material comprising silicon, lithium, carbon and SiC;
[0007] The microstructure of the highly uniform silicon-based composite material is a multiphase dispersed structure; the multiphase dispersed structure is obtained by uniformly mixing gaseous raw materials; the gaseous raw materials include: gaseous silicon / carbon composite material, gaseous silicon source material, and gaseous lithium source material;
[0008] The silicon / carbon composite material is obtained by blending and coating silicon powder with carbon source material.
[0009] The lithium element accounts for 0.5%-20% of the total mass of the highly uniform silicon-based composite material;
[0010] The carbon element accounts for 0.1%-10% of the total mass of the highly uniform silicon-based composite material;
[0011] The SiC accounts for 0.1%-10% of the total mass of the highly uniform silicon-based composite material;
[0012] The silicon source material includes: silicon powder or a mixture of silicon powder and silicon dioxide powder;
[0013] The carbon source material includes: inorganic carbon source material and / or organic carbon source material; the inorganic carbon source material includes one or more of graphene, multi-walled carbon nanotubes, single-walled carbon nanotubes, conductive carbon black, and conductive carbon fiber; the organic carbon source material includes one or more of asphalt, polyvinylidene fluoride, polyvinylpyrrolidone, phenolic resin, and sodium carboxymethyl cellulose.
[0014] The lithium source material includes: inorganic lithium source material and / or organic lithium source material; the inorganic lithium source material includes one or more of lithium carbonate, lithium nitride, lithium hydride, lithium oxide, lithium phosphate, lithium manganese oxide, lithium thiosulfate or metallic lithium; the organic lithium source material includes: butyllithium and / or phenyllithium.
[0015] The highly uniform silicon-based composite material further includes a carbon coating layer; the mass of the carbon coating layer accounts for 0-20% of the total mass of the modified silicon-based anode material.
[0016] In a second aspect, a method for preparing the highly uniform silicon-based composite material described in the first aspect above, the method comprising:
[0017] Silicon powder and carbon source materials are blended and coated to obtain silicon / carbon composite materials;
[0018] The silicon / carbon composite material, silicon source material and lithium source material are mixed evenly and placed in a vapor deposition furnace, and heated under reduced pressure to obtain a mixed gas source.
[0019] The mixed gas source is cooled and deposited on a stainless steel substrate to obtain a deposited material;
[0020] After the deposited material is crushed and sieved, a highly uniform silicon-based composite material is obtained.
[0021] The silicon source material includes: silicon powder or a mixture of silicon powder and silicon dioxide powder;
[0022] The carbon source material includes: inorganic carbon source material and / or organic carbon source material; the inorganic carbon source material includes one or more of graphene, multi-walled carbon nanotubes, single-walled carbon nanotubes, conductive carbon black, and conductive carbon fiber; the organic carbon source material includes one or more of asphalt, polyvinylidene fluoride, polyvinylpyrrolidone, phenolic resin, and sodium carboxymethyl cellulose.
[0023] The lithium source material includes: inorganic lithium source material and / or organic lithium source material; the inorganic lithium source material includes one or more of lithium carbonate, lithium nitride, lithium hydride, lithium oxide, lithium phosphate, lithium manganese oxide, lithium thiosulfate, or metallic lithium; the organic lithium source material includes: butyllithium and / or phenyllithium.
[0024] The lithium element accounts for 0.5%-20% of the total mass of the highly uniform silicon-based composite material;
[0025] The carbon element accounts for 0.1%-10% of the total mass of the highly uniform silicon-based composite material;
[0026] The SiC accounts for 0.1%-10% of the total mass of the highly uniform silicon-based composite material.
[0027] The blend coating includes one or more of the following: mechanical fusion coating, ball milling coating, hot pressing coating, cold pressing coating, or sand milling coating;
[0028] Specifically, the reduced pressure conditions refer to evacuating to a vacuum of 60Pa-200Pa; the heating temperature is between 1000℃ and 2000℃.
[0029] The preparation method further includes carbon coating the highly uniform silicon-based composite material;
[0030] The carbon coating method includes one or more of gas phase coating, liquid phase coating, and solid phase coating;
[0031] The carbon coating layer accounts for 0-20% of the total mass of the highly uniform silicon-based composite material.
[0032] Thirdly, a negative electrode sheet comprising the highly uniform silicon-based composite material described in the first aspect above.
[0033] Fourthly, a lithium battery comprising the negative electrode sheet described in the third aspect above.
[0034] This invention provides a highly uniform silicon-based composite material. First, silicon powder is blended and coated with a carbon source material to form a silicon / carbon composite material. Then, this composite material is mixed with silica powder and a lithium source material under reduced pressure to obtain a corresponding mixed gas source. The mixture is then rapidly cooled, deposited, and pulverized to obtain the highly uniform silicon-based composite material. On one hand, adding a lithium source material can compensate for irreversible lithium loss. On the other hand, by pre-coating the silicon powder and carbon source material to obtain the silicon / carbon composite material, some unreacted carbon elements and SiC generated under reduced pressure and high-temperature heat treatment can be uniformly dispersed at each stage of deposition, without any difference in content due to the order of deposition. This effectively ensures the uniformity of all deposited matrices, buffers volume expansion during charge and discharge, inhibits alloy pulverization, and enhances the conductivity of the silicon-based composite material. This invention's highly uniform silicon-based composite material, through the co-coating of carbon source material and silicon powder, and the combined action of doped lithium elements, yields a highly uniform silicon-based composite material of lithium, carbon, and SiC, thereby improving the battery's first-cycle coulombic efficiency, cycle performance, rate performance, and consistency. Attached Figure Description
[0035] The technical solutions of the embodiments of the present invention will be further described in detail below with reference to the accompanying drawings and examples.
[0036] Figure 1 This is a flowchart of a method for preparing highly uniform silicon-based composite materials according to an embodiment of the present invention;
[0037] Figure 2The X-ray diffraction (XRD) pattern of the highly uniform silicon-based composite material prepared in Example 1 of this invention. Detailed Implementation
[0038] The present invention will be further described in detail below with reference to the accompanying drawings and specific embodiments. However, it should be understood that these embodiments are only for more detailed description and should not be construed as limiting the present invention in any way, that is, not intended to limit the scope of protection of the present invention.
[0039] This embodiment provides a highly uniform silicon-based composite material, which includes silicon, lithium, carbon, and SiC; wherein lithium accounts for 0.5%-20% of the total mass of the highly uniform silicon-based composite material; carbon accounts for 0.1%-10% of the total mass of the highly uniform silicon-based composite material; and SiC accounts for 0.1%-10% of the total mass of the highly uniform silicon-based composite material.
[0040] The microstructure of the highly uniform silicon-based composite material is a multiphase dispersed structure; the multiphase dispersed structure is obtained by uniformly mixing gaseous raw materials; the gaseous raw materials include: gaseous silicon / carbon composite material, gaseous silicon source material, and gaseous lithium source material;
[0041] Silicon / carbon composite materials are obtained by blending and coating silicon powder and carbon source materials. By pre-blending and coating the carbon source on the surface of silicon powder, carbon elements can be evenly distributed in each stage of deposition, and its content does not differ due to the order of deposition, effectively ensuring the uniformity of all deposited matrices.
[0042] Among them, silicon source materials include: silicon powder or a mixture of silicon powder and silicon dioxide powder;
[0043] Carbon source materials include: inorganic carbon source materials and / or organic carbon source materials; inorganic carbon source materials include: one or more of graphene, multi-walled carbon nanotubes, single-walled carbon nanotubes, conductive carbon black, and conductive carbon fibers; organic carbon source materials include: one or more of pitch, polyvinylidene fluoride, polyvinylpyrrolidone, phenolic resin, and sodium carboxymethyl cellulose.
[0044] Lithium source materials include: inorganic lithium source materials and / or organic lithium source materials; inorganic lithium source materials include: one or more of lithium carbonate, lithium nitride, lithium hydride, lithium oxide, lithium phosphate, lithium manganese oxide, lithium thiosulfate or metallic lithium; organic lithium source materials include: butyllithium and / or phenyllithium.
[0045] In an optional configuration, the highly uniform silicon-based composite material also includes a carbon coating layer; the mass of the carbon coating layer accounts for 0-20% of the total mass of the modified silicon-based anode material.
[0046] This invention provides a method for preparing the above-mentioned highly uniform silicon-based composite material, such as... Figure 1 As shown, the preparation method includes:
[0047] Step 110: Silica powder and carbon source material are blended and coated to obtain silicon / carbon composite material;
[0048] Among them, blending coating includes one or more of the following: mechanical fusion coating, ball milling coating, hot pressing coating, cold pressing coating, or sand milling coating;
[0049] Carbon source materials include: inorganic carbon source materials and / or organic carbon source materials; inorganic carbon source materials include: one or more of graphene, multi-walled carbon nanotubes, single-walled carbon nanotubes, conductive carbon black, and conductive carbon fibers; organic carbon source materials include: one or more of pitch, polyvinylidene fluoride, polyvinylpyrrolidone, phenolic resin, and sodium carboxymethyl cellulose.
[0050] Step 120: Mix the silicon / carbon composite material, silicon source material and lithium source material evenly, place them in a vapor deposition furnace, and heat under reduced pressure to obtain a mixed gas source;
[0051] Specifically, under reduced pressure conditions, the vacuum is evacuated to 60Pa-200Pa; the heating temperature is between 1000℃ and 2000℃.
[0052] Silicon source materials include: silicon powder or a mixture of silicon powder and silicon dioxide powder;
[0053] Lithium source materials include: inorganic lithium source materials and / or organic lithium source materials; inorganic lithium source materials include: one or more of lithium carbonate, lithium nitride, lithium hydride, lithium oxide, lithium phosphate, lithium manganese oxide, lithium thiosulfate or metallic lithium; organic lithium source materials include: butyllithium and / or phenyllithium.
[0054] Step 130: Cool and deposit the mixed gas source on a stainless steel substrate to obtain the deposited material.
[0055] Step 140: After crushing and sieving the deposited material, a highly uniform silicon-based composite material is obtained.
[0056] Lithium accounts for 0.5%-20% of the total mass of the high-uniformity silicon-based composite material; carbon accounts for 0.1%-10% of the total mass of the high-uniformity silicon-based composite material; and SiC accounts for 0.1%-10% of the total mass of the high-uniformity silicon-based composite material.
[0057] In optional embodiments, the preparation method further includes carbon coating of the highly uniform silicon-based composite material; the carbon coating method includes one or more of gas phase coating, liquid phase coating, and solid phase coating; the mass of the carbon coating layer accounts for 0-20% of the total mass of the highly uniform silicon-based composite material.
[0058] This invention provides a negative electrode sheet comprising the highly uniform silicon-based composite material prepared above, which can be used in lithium batteries.
[0059] To better understand the technical solution provided by the present invention, the preparation process and characteristics of the high-uniformity silicon-based composite material of the present invention are illustrated below with several specific examples.
[0060] Example 1
[0061] This embodiment provides a method for preparing and testing the performance of a highly uniform silicon-based composite material.
[0062] The specific preparation process is as follows:
[0063] 1) Place 1.2 kg of silicon powder and 45 g of conductive carbon black into a ball mill for blending and coating. Dry mill for 12 hours at a speed of 600 r / min with both forward and reverse rotation to obtain silicon / carbon composite material.
[0064] 2) Add 1 kg of silica powder and 400 g of lithium nitride to the silicon / carbon composite material, mix them evenly, place them in a vapor deposition furnace, evacuate to 180 Pa, heat to 1800 ℃ and hold for 2 hours to obtain a mixed gas source.
[0065] 3) The mixed gas source is cooled and deposited on a stainless steel substrate to obtain the deposited material.
[0066] 4) After crushing and sieving the deposited material, a highly uniform silicon-based composite material is obtained.
[0067] The carbon content of the front, middle and rear sections of the deposition process was tested using a carbon-sulfur analyzer, and the results were 1.25%, 1.28% and 1.26%, respectively.
[0068] The prepared highly uniform silicon-based composite material was subjected to XRD testing, such as... Figure 2 As shown, a SiC crystallization peak appeared near 35.6°, indicating the formation of crystalline SiC.
[0069] 5) Carbon coating was performed on the prepared high-uniformity silicon-based composite material. Specifically, 1 kg of the high-uniformity silicon-based composite material was placed in a rotary kiln and heated to 1050°C under a protective atmosphere. Argon gas and an equal amount of ethylene and propane mixed gas were introduced at a volume ratio of 2:1 for gas phase coating. The volume ratio of ethylene and propane was 2:3. The temperature was maintained for 1 hour and the organic gas source was turned off. After cooling and grading, the high-uniformity silicon-based composite material with carbon coating was obtained. The carbon content was tested to be 2.8% using a carbon-sulfur analyzer.
[0070] The high-uniformity silicon-based composite material with carbon coating prepared in this embodiment was used to prepare a negative electrode sheet and assemble a battery for testing.
[0071] Preparation of negative electrode sheet: Weigh the negative electrode material, conductive additive, and binder obtained above in a ratio of 95%:2%:3%, and place them in a pulping machine at room temperature to prepare a slurry; uniformly coat the prepared slurry onto copper foil. After baking at 50°C in a forced-air drying oven for 2 hours, remove and cut into 8×8mm electrode sheets, and vacuum-bake at 100°C in a vacuum drying oven for 10 hours. Transfer the dried electrode sheets into a glove box for later use.
[0072] Battery assembly: The assembly of the simulated battery was carried out in a glove box containing a high-purity Ar atmosphere, using lithium metal as the counter electrode and a mixed solution of 1 mole of LiPF6 and ethylene carbonate / dimethyl carbonate (EC / DMC) as the electrolyte, to assemble the battery.
[0073] The battery was tested in constant current charge-discharge mode using a charge-discharge instrument: the discharge cutoff voltage was 0.005V and the charging cutoff voltage was 1.5V. The first week of charge-discharge test was conducted at a current density of 0.1C, and the second week of discharge test was conducted at a current density of 1C. The initial efficiency, 0.1C reversible capacity, and test results of 100 and 500 cycles at 1C rate of the battery assembled in this embodiment are detailed in Table 1.
[0074] Example 2
[0075] This embodiment provides a method for preparing and testing the performance of a highly uniform silicon-based composite material.
[0076] The specific preparation process is as follows:
[0077] 1) 2 kg of silicon powder and 80 g of graphene were fused in a fusion machine at a speed of 800 rpm for 17 hours to obtain a silicon / carbon composite material.
[0078] 2) Add 1 kg of silica powder and 260 g of lithium phosphate to the silicon / carbon composite material, mix them evenly, place them in a vapor deposition furnace, evacuate to 160 Pa, heat to 1600 ℃ and hold for 3 hours to obtain a mixed gas source.
[0079] 3) The mixed gas source is cooled and deposited on a stainless steel substrate to obtain the deposited material.
[0080] 4) After crushing and sieving the deposited material, a highly uniform silicon-based composite material is obtained.
[0081] The carbon content of the front, middle and rear sections of the deposition process was tested using a carbon-sulfur analyzer, and the results were 2.32%, 2.33% and 2.30%, respectively.
[0082] 5) Carbon coating was performed on the prepared high-uniformity silicon-based composite material. Specifically, 1 kg of the high-uniformity silicon-based composite material was placed in a rotary kiln and heated to 850°C under a protective atmosphere. Argon gas and an equal amount of acetylene and ethane gas were introduced at a volume ratio of 1:2 for gas phase coating. The volume ratio of acetylene and ethane was 1:1. The temperature was maintained for 2 hours and the organic gas source was turned off. After cooling and grading, the high-uniformity silicon-based composite material with a carbon coating layer was obtained. The carbon content was tested to be 4.5% using a carbon-sulfur analyzer.
[0083] The high-uniformity silicon-based composite material with carbon coating prepared in this embodiment was used to prepare a negative electrode sheet, and a battery was assembled and tested. The specific process was the same as in Example 1. The test data are detailed in Table 1.
[0084] Example 3
[0085] This embodiment provides a method for preparing and testing the performance of a highly uniform silicon-based composite material.
[0086] The specific preparation process is as follows:
[0087] 1) Mix 1.5 kg of silicon powder and 60 g of single-walled carbon nanotubes evenly, place them in a hot press, and hot press them at 200 °C and 12 MPa for 1 hour to obtain silicon / carbon composite material.
[0088] 2) Mix 1 kg of silica powder and 800 g of lithium carbonate evenly in the silicon / carbon composite material, place it in a vapor deposition furnace, evacuate to 150 Pa, heat to 1700 °C and hold for 1.5 hours to obtain a mixed gas source.
[0089] 3) The mixed gas source is cooled and deposited on a stainless steel substrate to obtain the deposited material.
[0090] 4) After crushing and sieving the deposited material, a highly uniform silicon-based composite material is obtained.
[0091] The carbon content of the front, middle and rear sections of the deposition process was tested using a carbon-sulfur analyzer, and the results were 1.79%, 1.80% and 1.79%, respectively.
[0092] 5) Carbon coating was performed on the prepared high-uniformity silicon-based composite material. Specifically, 1 kg of the high-uniformity silicon-based composite material was placed in a rotary kiln and heated to 950°C under a protective atmosphere. Argon and acetylene were introduced at a volume ratio of 1:2.25 for gas phase coating. The temperature was maintained for 3 hours and the organic gas source was turned off. After cooling and grading, the high-uniformity silicon-based composite material with carbon coating was obtained. The carbon content was tested to be 4.8% using a carbon-sulfur analyzer.
[0093] The high-uniformity silicon-based composite material with carbon coating prepared in this embodiment was used to prepare a negative electrode sheet, and a battery was assembled and tested. The specific process was the same as in Example 1. The test data are detailed in Table 1.
[0094] Example 4
[0095] This embodiment provides a method for preparing and testing the performance of a highly uniform silicon-based composite material.
[0096] The specific preparation process is as follows:
[0097] 1) Mix 1kg of silicon powder, 15g of multi-walled carbon nanotubes and 30g of phenolic resin evenly, place them in a cold press, and cold press at a pressure of 25 tons for 24 hours to obtain silicon / carbon composite material.
[0098] 2) Add 1 kg of silica powder and 1 kg of lithium thiosulfate to the silicon / carbon composite material, mix them evenly, place them in a vapor deposition furnace, evacuate to 100 Pa, heat to 1800℃ and hold for 1 hour to obtain a mixed gas source.
[0099] 3) The mixed gas source is cooled and deposited on a stainless steel substrate to obtain the deposited material.
[0100] 4) After crushing and sieving the deposited material, a highly uniform silicon-based composite material is obtained.
[0101] The carbon content of the front, middle and rear sections of the deposition process was tested using a carbon-sulfur analyzer, and the results were 2.09%, 2.11% and 2.11%, respectively.
[0102] The high-uniformity silicon-based composite material without carbon coating prepared in this embodiment was used to prepare a negative electrode sheet, and a battery was assembled and tested. The specific process was the same as in Example 1. The test data are detailed in Table 1.
[0103] Example 5
[0104] This embodiment provides a method for preparing and testing the performance of a highly uniform silicon-based composite material.
[0105] The specific preparation process is as follows:
[0106] 1) Mix 1kg of silicon powder and 120g of asphalt evenly, place them in a sand mill, set the linear speed to 12m / s, and sand mill for 10 hours to obtain silicon / carbon composite material.
[0107] 2) Add 1 kg of silica powder and 800 g of lithium manganese oxide to the silicon / carbon composite material, mix them evenly, place them in a vapor deposition furnace, evacuate to 150 Pa, heat to 1700 ℃ and hold for 1.5 hours to obtain a mixed gas source.
[0108] 3) The mixed gas source is cooled and deposited on a stainless steel substrate to obtain the deposited material.
[0109] 4) After crushing and sieving the deposited material, a highly uniform silicon-based composite material is obtained.
[0110] The carbon content of the front, middle and rear sections of the deposition process was tested using a carbon-sulfur analyzer, and the results were 1.69%, 1.68% and 1.70%, respectively.
[0111] 5) Carbon coating was performed on the prepared high-uniformity silicon-based composite material. Specifically, 1 kg of high-uniformity silicon-based composite material and graphene were dissolved in n-butanol at a ratio of 23:1 and stirred for 6 hours to form a uniform slurry. After drying the slurry, it was placed in a rotary kiln and heated to 1000℃ under a protective atmosphere for 2 hours. After cooling and grading, the high-uniformity silicon-based composite material with carbon coating was obtained. The carbon content was tested to be 2.9% using a carbon-sulfur analyzer.
[0112] The high-uniformity silicon-based composite material with carbon coating prepared in this embodiment was used to prepare a negative electrode sheet, and a battery was assembled and tested. The specific process was the same as in Example 1. The test data are detailed in Table 1.
[0113] Example 6
[0114] This embodiment provides a method for preparing and testing the performance of a highly uniform silicon-based composite material.
[0115] The specific preparation process is as follows:
[0116] 1) Mix 1 kg of silicon powder and 160 g of polyvinylpyrrolidone evenly, place them in a hot press, and hot press for 1 hour at 150°C and 20 MPa to obtain silicon / carbon composite material.
[0117] 2) Add 1 kg of silica powder and 500 g of phenyl lithium to the silicon / carbon composite material, mix them evenly, place them in a vapor deposition furnace, evacuate to 60 Pa, heat to 2000 ℃ and hold for 2.5 hours to obtain a mixed gas source.
[0118] 3) The mixed gas source is cooled and deposited on a stainless steel substrate to obtain the deposited material.
[0119] 4) After crushing and sieving the deposited material, a highly uniform silicon-based composite material is obtained.
[0120] The carbon content of the front, middle and rear sections of the deposition process was tested using a carbon-sulfur analyzer, and the results were 1.18%, 1.21% and 1.17%, respectively.
[0121] 5) Carbon coating was performed on the prepared high-uniformity silicon-based composite material. Specifically, 1 kg of high-uniformity silicon-based composite material and phenolic resin were dissolved in tetrahydrofuran at a ratio of 17:1 and stirred for 8 hours to form a uniform slurry. After drying the slurry, it was placed in a rotary kiln and heated to 850°C for 3 hours under a protective atmosphere. After cooling and grading, the high-uniformity silicon-based composite material with carbon coating was obtained. The carbon content was tested to be 4.4% using a carbon-sulfur analyzer.
[0122] The high-uniformity silicon-based composite material with carbon coating prepared in this embodiment was used to prepare a negative electrode sheet, and a battery was assembled and tested. The specific process was the same as in Example 1. The test data are detailed in Table 1.
[0123] Example 7
[0124] This embodiment provides a method for preparing and testing the performance of a highly uniform silicon-based composite material.
[0125] The specific preparation process is as follows:
[0126] 1) Mix 1 kg of silicon powder and 200 g of sodium carboxymethyl cellulose evenly, place them in a ball mill, and ball mill at 800 r / min for 24 hours to obtain silicon / carbon composite material.
[0127] 2) Add 1 kg of silica powder and 150 g of lithium metal to the silicon / carbon composite material, mix them evenly, place them in a vapor deposition furnace, evacuate to 160 Pa, heat to 1700 ℃ and hold for 2 hours to obtain a mixed gas source.
[0128] 3) The mixed gas source is cooled and deposited on a stainless steel substrate to obtain the deposited material.
[0129] 4) After crushing and sieving the deposited material, a highly uniform silicon-based composite material is obtained.
[0130] The carbon content of the front, middle and rear sections of the deposition process was tested using a carbon-sulfur analyzer, and the results were 1.52%, 1.53% and 1.50%, respectively.
[0131] 5) Carbon coating was applied to the prepared high-uniformity silicon-based composite material. Specifically, 1 kg of high-uniformity silicon-based composite material was mixed with asphalt emulsion at a mass ratio of 11:1 and stirred for 4 hours to form a uniform slurry. After drying the slurry, it was placed in a rotary kiln and heated to 850℃ for 2 hours under a protective atmosphere. After cooling and grading, the high-uniformity silicon-based composite material with carbon coating was obtained. The carbon content was tested to be 5.4% using a carbon-sulfur analyzer.
[0132] The high-uniformity silicon-based composite material with carbon coating prepared in this embodiment was used to prepare a negative electrode sheet, and a battery was assembled and tested. The specific process was the same as in Example 1. The test data are detailed in Table 1.
[0133] Example 8
[0134] This embodiment provides a method for preparing and testing the performance of a highly uniform silicon-based composite material.
[0135] The specific preparation process is as follows:
[0136] 1) After mixing 1kg of silicon powder and 230g of polyvinylidene fluoride evenly, place them in a cold press, set the pressure to 40 tons, and cold press for 20 hours to obtain silicon / carbon composite material.
[0137] 2) Add 1 kg of silica powder and 700 g of butyllithium to the silicon / carbon composite material, mix them evenly, place them in a vapor deposition furnace, evacuate to 200 Pa, heat to 1000 °C and hold for 2.5 hours to obtain a mixed gas source.
[0138] 3) The mixed gas source is cooled and deposited on a stainless steel substrate to obtain the deposited material.
[0139] 4) After crushing and sieving the deposited material, a highly uniform silicon-based composite material is obtained.
[0140] The carbon content of the front, middle and rear sections of the deposition process was tested using a carbon-sulfur analyzer, and the results were 2.68%, 2.70% and 2.67%, respectively.
[0141] 5) Carbon coating was performed on the prepared high-uniformity silicon-based composite material. Specifically, 1 kg of the high-uniformity silicon-based composite material was placed in a rotary kiln and heated to 1050°C under a protective atmosphere. Argon and propylene gases were introduced at a volume ratio of 1:1.5 for gas phase coating. The temperature was maintained for 3 hours and the organic gas source was turned off. After cooling and grading, the high-uniformity silicon-based composite material with carbon coating was obtained. The carbon content was tested to be 5.2% using a carbon-sulfur analyzer.
[0142] The high-uniformity silicon-based composite material with carbon coating prepared in this embodiment was used to prepare a negative electrode sheet, and a battery was assembled and tested. The specific process was the same as in Example 1. The test data are detailed in Table 1.
[0143] To better illustrate the effects of the embodiments of the present invention, comparative examples 1-3 are compared with the above embodiments.
[0144] Example 9
[0145] This embodiment provides a method for preparing and testing the performance of a highly uniform silicon-based composite material.
[0146] The specific preparation process is as follows:
[0147] 1) 1 kg of silicon powder and 180 g of phenolic resin were fused in a fusion machine at a speed of 1000 rpm for 9 hours to obtain a silicon / carbon composite material.
[0148] 2) Add 1 kg of silica powder and 180 g of lithium oxide to the silicon / carbon composite material, mix them evenly, place them in a vapor deposition furnace, evacuate to 190 Pa, heat to 1800 ℃ and hold for 3 hours to obtain a mixed gas source.
[0149] 3) The mixed gas source is cooled and deposited on a stainless steel substrate to obtain the deposited material.
[0150] 4) After crushing and sieving the deposited material, a highly uniform silicon-based composite material is obtained.
[0151] The carbon content of the front, middle and rear sections of the deposition process was tested using a carbon-sulfur analyzer, and the results were 1.72%, 1.73% and 1.70%, respectively.
[0152] 5) Carbon coating was applied to the prepared high-uniformity silicon-based composite material. Specifically, 1 kg of high-uniformity silicon-based composite material was mixed with petroleum asphalt at a mass ratio of 11:1, placed in a rotary kiln, heated to 1000℃ under a protective atmosphere, held for 2.5 hours, cooled, discharged, and graded to obtain a high-uniformity silicon-based composite material with a carbon coating layer. The carbon content was tested to be 3.9% using a carbon-sulfur analyzer.
[0153] The high-uniformity silicon-based composite material with carbon coating prepared in this embodiment was used to prepare a negative electrode sheet, and a battery was assembled and tested. The specific process was the same as in Example 1. The test data are detailed in Table 1.
[0154] Comparative Example 1
[0155] This comparative example provides a method for preparing and testing the performance of a silicon-based material that is not co-coated with silicon powder and is not doped with lithium.
[0156] The specific preparation process is as follows:
[0157] 1) Place 1 kg of silicon powder and 1 kg of silicon dioxide powder in a vapor deposition furnace and heat them to obtain a mixed gas source.
[0158] 2) The mixed gas source is cooled and deposited on a stainless steel substrate to obtain the deposited material.
[0159] 3) After crushing and sieving the deposited material, a silicon-based composite material is obtained.
[0160] The negative electrode sheet was prepared using the silicon-based material without carbon coating prepared in this comparative example, and a battery was assembled and tested. The specific process was the same as in Example 1. The test data are detailed in Table 1.
[0161] Comparative Example 2
[0162] This comparative example provides a method for preparing and testing the performance of a silicon-based composite material that is not co-coated with silicon powder but is doped with lithium.
[0163] The specific preparation process is as follows:
[0164] 1) Mix 1 kg of silicon powder, 1 kg of silica powder and 100 g of lithium hydride evenly, place them in a vapor deposition furnace, evacuate to 80 Pa, heat to 1700 °C and hold for 2 hours to obtain a mixed gas source.
[0165] 2) The mixed gas source is cooled and deposited on a stainless steel substrate to obtain the deposited material.
[0166] 3) After crushing and sieving the deposited material, a silicon-based composite material is obtained.
[0167] 4) Carbon coating is applied to the prepared silicon-based composite material. Specifically, 1 kg of silicon-based composite material is mixed with petroleum asphalt at a mass ratio of 22:1, placed in a high-temperature furnace, and kept at 1000℃ for 1.5 hours under a protective atmosphere. After cooling and discharging and grading, lithium-ion silicon-based composite material with carbon coating is obtained, wherein the total carbon content is 3.1%.
[0168] The silicon-based composite material with carbon coating prepared in this comparative example was used to prepare a negative electrode sheet and assemble a battery for testing. The specific process was the same as in Example 1. The test data are detailed in Table 1.
[0169] Comparative Example 3
[0170] This comparative example provides a method for preparing and testing the performance of a silicon-based composite material using blended coated silicon powder but without lithium doping.
[0171] The specific preparation process is as follows:
[0172] 1) Mix 1 kg of silicon powder and 40 g of conductive carbon fiber evenly, place them in a ball mill, set the speed to 400 r / min, and ball mill for 20 hours with forward and reverse rotation to obtain silicon / carbon composite material.
[0173] 2) Mix evenly with 1 kg of silica powder, place in the vapor deposition furnace cavity, evacuate to 190 Pa, heat to 1600℃ and hold for 3 hours to obtain a mixed gas source.
[0174] 3) The mixed gas source is cooled and deposited on a stainless steel substrate to obtain the deposited material.
[0175] 4) After crushing and sieving the deposited material, a silicon-based composite material is obtained.
[0176] The carbon content of the front, middle and rear sections of the deposit was tested using a carbon-sulfur analyzer and found to be 1.29%, 1.31% and 1.30%, respectively.
[0177] 5) Carbon coating was applied to the prepared silicon-based composite material. Specifically, 1 kg of silicon-based composite material and phenolic resin were dissolved in acetone at a ratio of 25:1 and stirred for 5 hours to form a uniform slurry. After drying the slurry, it was placed in a rotary kiln and heated to 1000℃ under a protective atmosphere for 2 hours. After cooling and grading, the silicon-based composite material with a carbon coating layer was obtained. The carbon content was tested to be 4.1% using a carbon-sulfur analyzer.
[0178] The silicon-based composite material with carbon coating prepared in this comparative example was used to prepare a negative electrode sheet and assemble a battery for testing. The specific process was the same as in Example 1. The test data are detailed in Table 1.
[0179] The anode materials in Examples 1-8 and Comparative Examples 1-3 were tested for initial efficiency, reversible capacity at 0.1C rate, and cycle performance at 1C rate. The results are shown in Table 1.
[0180]
[0181] Table 1
[0182] As can be seen from the data comparison of Comparative Examples 1-3 in Table 1, Comparative Example 2, which doped the silicon-based composite material with lithium, significantly improved the initial efficiency compared to the silicon-based material of Comparative Example 1, which did not undergo any doping or blending process. However, its cycle performance was inferior. In the preparation process of the silicon-based composite material of Comparative Example 3, silicon powder was first blended with carbon to form a silicon / carbon composite material. Carbon was introduced in advance to uniformly coat the silicon particles. Compared to Comparative Examples 1 and 2, the cycle capacity retention rate was significantly improved. However, the initial efficiency was slightly inferior.
[0183] A comparison of the data from Examples 1-8 and Comparative Examples 1-3 in the table shows that, under the same test conditions, Examples 1-8 demonstrate superior initial efficiency and cycle performance compared to Comparative Examples 1 and 3 in preparing highly uniform silicon-based composite materials. This is because Examples 1-8, by pre-coating silicon powder with carbon source materials to obtain silicon / carbon composite materials, ensure that carbon elements and SiC generated under reduced pressure and high-temperature heat treatment are uniformly distributed throughout the deposition process, without any difference in content due to the order of deposition. This effectively guarantees the uniformity of all deposited substrates, buffers volume expansion during charge and discharge, inhibits alloy pulverization, and enhances the conductivity of the silicon-based composite material. Furthermore, the addition of lithium source materials compensates for lithium loss during the first charge and discharge cycle, thereby improving the battery's first-cycle coulombic efficiency, cycle performance, rate performance, and consistency.
[0184] The specific embodiments described above further illustrate the purpose, technical solution, and beneficial effects of the present invention. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A highly uniform silicon-based composite material, characterized in that, The highly uniform silicon-based composite material includes silicon, lithium, and carbon. The microstructure of the highly uniform silicon-based composite material is a multiphase dispersed structure; the multiphase dispersed structure is obtained by uniformly mixing gaseous raw materials; the gaseous raw materials include: gaseous silicon / carbon composite material, gaseous silicon source material, and gaseous lithium source material; The silicon / carbon composite material is obtained by one or more of the following methods: mechanical fusion coating, ball milling coating, hot pressing coating, cold pressing coating, or sand milling coating. The preparation method of the highly uniform silicon-based composite material includes: blending and coating silicon powder with carbon source material to obtain a silicon / carbon composite material; mixing the silicon / carbon composite material, silicon source material, and lithium source material uniformly, placing them in a vapor deposition furnace, and heating them under reduced pressure to obtain a mixed gas source; cooling and depositing the mixed gas source on a stainless steel substrate to obtain a deposited material; and pulverizing and sieving the deposited material to obtain a highly uniform silicon-based composite material with the formation of crystalline SiC. The SiC constitutes 0.1%-10% of the total mass of the highly uniform silicon-based composite material. The silicon source material includes: silicon powder or a mixture of silicon powder and silicon dioxide powder; The lithium source material includes: inorganic lithium source material and / or organic lithium source material; the inorganic lithium source material includes one or more of lithium carbonate, lithium nitride, lithium hydride, lithium oxide, lithium phosphate, lithium manganese oxide, lithium thiosulfate, or metallic lithium; the organic lithium source material includes: butyllithium and / or phenyllithium. Specifically, the reduced pressure conditions refer to evacuating to a vacuum of 60Pa-200Pa; the heating temperature is between 1000℃ and 2000℃.
2. The highly uniform silicon-based composite material according to claim 1, characterized in that, The lithium element accounts for 0.5%-20% of the total mass of the highly uniform silicon-based composite material; the carbon element accounts for 0.1%-10% of the total mass of the highly uniform silicon-based composite material.
3. The highly uniform silicon-based composite material according to claim 1, characterized in that, The carbon source material includes: inorganic carbon source material and / or organic carbon source material; the inorganic carbon source material includes one or more of graphene, multi-walled carbon nanotubes, single-walled carbon nanotubes, conductive carbon black, and conductive carbon fiber; the organic carbon source material includes one or more of asphalt, polyvinylidene fluoride, polyvinylpyrrolidone, phenolic resin, and sodium carboxymethyl cellulose.
4. A method for preparing a highly uniform silicon-based composite material according to any one of claims 1-3, characterized in that, The preparation method includes: Silicon powder and carbon source materials are blended and coated to obtain silicon / carbon composite materials; The silicon / carbon composite material, silicon source material and lithium source material are mixed evenly and placed in a vapor deposition furnace, and heated under reduced pressure to obtain a mixed gas source. The mixed gas source is cooled and deposited on a stainless steel substrate to obtain a deposited material; After the deposited material is crushed and sieved, a highly uniform silicon-based composite material is obtained, in which crystalline SiC is formed; wherein, the SiC accounts for 0.1%-10% of the total mass of the highly uniform silicon-based composite material; The silicon source material includes: silicon powder or a mixture of silicon powder and silicon dioxide powder; the lithium source material includes: inorganic lithium source material and / or organic lithium source material; The inorganic lithium source material includes one or more of lithium carbonate, lithium nitride, lithium hydride, lithium oxide, lithium phosphate, lithium manganese oxide, lithium thiosulfate, or metallic lithium; the organic lithium source material includes butyllithium and / or phenyllithium. The blend coating includes one or more of the following: mechanical fusion coating, ball milling coating, hot pressing coating, cold pressing coating, or sand milling coating; Specifically, the reduced pressure conditions refer to evacuating to a vacuum of 60Pa-200Pa; the heating temperature is between 1000℃ and 2000℃.
5. The preparation method according to claim 4, characterized in that, The carbon source material includes: inorganic carbon source material and / or organic carbon source material; the inorganic carbon source material includes one or more of graphene, multi-walled carbon nanotubes, single-walled carbon nanotubes, conductive carbon black, and conductive carbon fiber; the organic carbon source material includes one or more of asphalt, polyvinylidene fluoride, polyvinylpyrrolidone, phenolic resin, and sodium carboxymethyl cellulose. The lithium element accounts for 0.5%-20% of the total mass of the highly uniform silicon-based composite material; The carbon element accounts for 0.1%-10% of the total mass of the highly uniform silicon-based composite material.
6. The preparation method according to claim 4, characterized in that, The preparation method further includes carbon coating the highly uniform silicon-based composite material; The carbon coating method includes one or more of gas phase coating, liquid phase coating, and solid phase coating.
7. A negative electrode sheet, characterized in that, The high-uniformity silicon-based composite material includes any one of the claims 1-3 above.
8. A lithium battery, characterized in that, Includes the negative electrode sheet as described in claim 7 above.
Citation Information
Patent Citations
Silicon carbon composite material and preparation method and application thereof
CN110289412A
Uniformly modified silicon-based composite material as well as preparation method and application thereof
CN113437271A